Resistance Training Combined With Stretching Increases Tendon Stiffness and Is More Effective Than Stretching Alone in Children With Cerebral Palsy: A Randomized Controlled Trial - Kalkman, Barbara M.; Holmes, Gill; Bar-On, Lynn; Maganaris, Constantinos N.; Barton, Gabor J.; Bass, Alfie; Wright, David M.; Walton, Roger; O'Brien, Thomas D. (Frontiers in Pediatrics, 2019)
Aim: Stretching is often used to increase/maintain muscle length and improve joint range of motion (ROM) in children with cerebral palsy (CP). However, outcomes at the muscle (remodelling) and resulting function appear to be highly variable and often unsatisfactory. During passive joint rotation, the Achilles tendon lengthens more than the in-series medial gastrocnemius muscle in children with CP, which might explain the limited effectiveness of stretching interventions. We aimed to ascertain whether increasing tendon stiffness, by performing resistance training, improves the effectiveness of passive stretching, indicated by an increase in medial gastrocnemius fascicle length. Methods: Sixteen children with CP (Age median [IQR]: 9.6 [8.6, 10.5]) completed the study. Children were randomly assigned to a combined intervention of stretching and strengthening of the calf muscles (n=9) or a control (stretching-only) group (n=7). Medial gastrocnemius fascicle length at a resting ankle angle, lengthening during passive joint rotations and tendon stiffness were assessed by combining dynamometry and ultrasound imaging. The study was registered on clinicaltrials.gov (NCT02766491). Results: Resting fascicle length and tendon stiffness increased more in the intervention group compared to the control group (median [95% CI] increase fascicle length: 2.2 [1.3, 4.3] mm; stiffness: 13.6 [9.9, 17.7] N/mm) Maximum dorsiflexion angle increased equally in both groups. Conclusion: This study provides proof of principle that a combined resistance and stretching intervention can increase tendon stiffness and muscle fascicle length in children with CP. This demonstrates that remodelling of muscle structure is possible with non-invasive interventions in spastic CP